108 Palliative care for neonates: Retrospective mixed methods review of infant death in the Neonatal Intensive Care Unit. (19th August 2020) - Journault, Marina; Stenekes, Simone; McClure, Robin; Ruth, Chelsea
Abstract: Background: Neonatal palliative care is an under researched yet growing field in the provision of intensive care to neonates. There are currently no studies which explore infant death in the Neonatal Intensive Care Unit (NICU) itself where a shift from intensive to palliative care may occur. Objectives: The purpose of this study was to explore the circumstances of infant death in the NICU and understand current utilization of specialist palliative care in this area. It aimed to characterize the infants' clinical course and add unique understanding by analyzing documentation related to end of life care. Design/Methods: A retrospective chart review of infants who died in a single centre NICU between January 2017 and March 2018 was undertaken. Infants of any gestational and post-natal age were included, excluding infants who died prior to arrival to the NICU or were discharged or transferred prior to death. Chart notes relating to prognosis, advanced care planning, and palliative interventions were sampled, coded, and collated for thematic analysis. Results: Twenty-five infants met study criteria. Of these, 92% were preterm with more than half below 28 weeks gestation. Median age at death was 5.2 days (IQR 1, 26.2). All infants required ventilator support with planned withdrawal occurring in 60%. Specialist palliative care was involved in 28%; these infants tended to be older (mean age at death = 78 days). Most infants were labelled as "critical" 2-5 days prior to death. Seventy-six percent of infants were held on their last day of life with 72% of families having memory making documented as part of their care. Qualitative excerpts revealed themes of hope and acceptance, parental presence, and framed discussion. Within these emerged concepts of "parental agreement" and "palliative language/approach". Conclusion: There is a growing need for both primary and specialist palliative care in the NICU. This study highlights an under researched area and generates many more important questions. By exploring documented language, we aim to understand and improve the ability to frame the discussion while ensuring quality end of life care for dying infants and their families in the NICU.